2018
DOI: 10.1002/lt.25072
|View full text |Cite|
|
Sign up to set email alerts
|

Should organs from hepatitis C‐positive donors be used in hepatitis C‐negative recipients for liver transplantation?

Abstract: Given the scarcity of donated organs and the frequency of death on the waiting list, strategies that could improve the available supply of high-quality liver grafts are much needed. Direct-acting antiviral agent (DAA) regimens have proved to be highly effective to treat hepatitis C virus (HCV), even in the setting of posttransplantation. The question arises as to whether transplant communities should consider the utilization of HCV-positive donors into HCV-negative recipients. This review summarizes risk of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…All donors undergo HCV‐antibody testing and nucleic acid testing for HCV RNA. Donors who are HCV antibody–positive and HCV RNA–negative pose a very low risk of HCV transmission to the recipient . Rarely, high‐risk donors with very recent HCV exposure who are anti‐HCV‐positive and HCV RNA–negative may pose a transmission risk .…”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
“…All donors undergo HCV‐antibody testing and nucleic acid testing for HCV RNA. Donors who are HCV antibody–positive and HCV RNA–negative pose a very low risk of HCV transmission to the recipient . Rarely, high‐risk donors with very recent HCV exposure who are anti‐HCV‐positive and HCV RNA–negative may pose a transmission risk .…”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
“…Discard of HCV + donor organs should be reconsidered because DAA therapy has revolutionized HCV treatment via well‐tolerated, highly effective regimens (Table ) exhibiting sustained virological response rates (SVR12) greater than 95% . Several large series demonstrate that DAA therapy is equally effective among HCV + transplant recipients, with cure rates near 100% predominately using 12‐week, interferon‐ and ribavirin‐free regimens . As a result of these data, national guidelines clearly support the use of DAAs to cure HCV post transplant…”
Section: Hcv+ Organs Are Increasingly Available Yet Frequently Discardedmentioning
confidence: 99%
“…In the United States, the rate of death from drug overdoses has increased exponentially . Using the United Network for Organ Sharing database from 2015 to 2016, Kling et al showed that 4.35% of all donors were viremic for HCV, and this number is increasing with the opioid epidemic .…”
mentioning
confidence: 99%
“…Using the United Network for Organ Sharing database from 2015 to 2016, Kling et al showed that 4.35% of all donors were viremic for HCV, and this number is increasing with the opioid epidemic . The transplant community’s interest in the use of HCV positive donors for HCV negative recipients has recently increased . However, it is controversial which HCV negative patients should receive those livers .…”
mentioning
confidence: 99%
See 1 more Smart Citation